Microbial Ecology in the North Pacific Subtropical Gyre - Matthew J. Church (Frontiers Research Topics, 2018)
The microbial community in the oligotrophic North Pacific Subtropical Gyre is dominated by unicellular microorganisms less than a few micrometers in size. Despite the persistent low nutrient concentrations, phytoplankton growth rates appear near maximal, sustained by the recycling of nutrients with plankton population sizes regulated by processes such as zooplankton grazing and viral lysis. Seasonal pulses of particle export to the deep sea and increases in phytoplankton abundance occur during the summer months; however, the factors that result in these imbalances in growth and loss processes are not well understood. Nonetheless, as a result of persistent fieldwork and development of sensitive methodologies, the biogeochemical and ecological dynamics occurring over timescales ranging from diel to interannual are being revealed. This Research Topic covers multiple aspects of microbial oceanography in the oligotrophic North Pacific Subtropical Gyre including identification and isolation of microorganisms, quantification of microbial biomass and turnover, metabolism and physiological activities, and microbial-mediated biogeochemical cycling. All of the papers use field data collected by either the Hawaii Ocean Time-series (HOT) program, the Center for Microbial Oceanography: Research and Education (C-MORE) or the Simons Collaboration on Ocean Processes and Ecology (SCOPE). These three programs have greatly increased our understanding of microbial ecology and biogeochemical cycling in the NPSG, in part by providing unparalleled access to the NPSG on oceanographic research vessels.